An Inter-Temporal Comparison About the Effect of Institutional Changes on the Policy-Making Process in Chile’S Health Sector - Olavarria-Gambi, M (Springer, 2022)
Do institutional changes lead to changes in the policy formulation process (PFP)? The paper analyses the health sector PFP of the old Chilean democracy (in place until 1973), until mid 1950s, and contrasts its finding with that of the democratic regime in place since 1990. Deep institutional reforms occurred in between, during the 17-year dictatorship of General Pinochet. The article concludes that both PFP behave similarly, raising the question of why is that and what might explain it. Information comes from official documents, press clippings, diverse literature and interviews. The article combines policy analysis with documental historical and hermeneutical methods. © 2021, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.